PENINGKATAN KINERJA PEGAWAI MELALUI GAYA KEPEMIMPINAN DAN KETERIKATAN KERJA PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI BANTEN - M Abdul Aziz; Ende Ende; Riza Wijayanti (Universitas Bina Bangsa, 2021)
Conditions related to employee performance that impacts the performance of diamonds at the Badan Perencanaan Pembangunan Daerah (BAPPEDA) Banten Province. This is because it is signaled that there are some problems based on the observations of researchers. This study aims to examine the influence between Leadership Style and Work Engagement with Employee Performance in BAPPEDA Banten Province. By using a descriptive approach to analysty which is quantitative research. Based on the research analysis obtained the value of coefficient of determination (R2)=40,3%. Partial test results of variable X1 of 3,593 and X2 of 3,275 were greater than 1,998 and sig. values < 0.05. The results of the study simultaneously obtained the results of Fcount = 20,922 > Ftable = 3,150. Based on the results of the study, it can be concluded that the influence of the variable Leadership Style and Work Engagement partially and simultaneously on Employee Performance has a significant and positive influence